Air conditioning analysis among human nasal passages with anterior anatomical variations. (July 2018) - Ma, Jiawei; Dong, Jingliang; Shang, Yidan; Inthavong, Kiao; Tu, Jiyuan; Frank-Ito, Dennis O.
Highlights: Nasal subjects with distinct anatomical variations are collected and categorised. The vestibule effect on air conditioning performance is numerically investigated. Increased heat and mass transfer rates are found at notched regions. Abstract: A major functional role of the nasal cavity is air conditioning of the inspired environmental air to near alveolar conditions. It is well known that the anatomical disparities among nasal passages can change airflow patterns to a great extent. However, its effect on nasal air conditioning performance remains largely unexplored. This research investigated the nasal air conditioning performance among nasal models with distinct vestibule phenotypes, including subjects with and without vestibule notches. For the mass transfer, we used a two-film theory model to determine the species transport. Airflow patterns, heat and mass transfer between the inhaled airflow and the nasal mucosa were analysed and compared. Results showed that the nasal air conditioning performance is closely related to nasal passage structures. The anatomical variations, especially the geometry changes in the anterior vestibule region, can increase both heat and mass transfer rate between nasal mucous and respiratory air at the vicinity of the notched regions, while for other regions such as the anterior superior nasal cavity, the heat transfer is greatly reduced to even zero heat flux due to lack of active airflow passing.